Identification of Genes Encoded Toxin-Antitoxin System in Mycobacterium Tuberculosis Strains from Clinical Sample - Sundaram, Karthikeyan; Kagithakara Vajravelu, Leela; Velayutham, Ravichandiran; Mohan, Utpal (Infectious Disorders - Drug Targets, 2024)
Background: The toxin-antitoxin system is a genetic element that is highly present in Mycobacterium tuberculosis (MTB), the causative agent of tuberculosis. The toxin-antitoxin system comprises toxin protein and antitoxin protein or non-encoded RNA interacting with each other and inhibiting toxin activity. M. Tuberculosis has more classes of TA loci than non-tubercle bacilli and other microbes, including VapBC, HigBA, MazEF, ParDE, RelBE, MbcTA, PemIK, DarTG, MenTA, one tripartite type II TAC chaperone system, and hypothetical proteins. Aims: The study aims to demonstrate the genes encoded toxin-antitoxin system in mycobacterium tuberculosis strains from clinical samples. Materials and Methods: The pulmonary and extra-pulmonary tuberculosis clinical samples were collected, and smear microscopy (Ziehl-Neelsen staining) was performed for the detection of high bacilli (3+) count, followed by nucleic acid amplification assay. Bacterial culture and growth assay, genomic DNA extraction, and polymerase chain reaction were also carried out. Results: The positive PTB and EPTB samples were determined by 3+ in microscopy smear and the total count of tubercle bacilli determined by NAAT assay was 8.0×1005in sputum and 1.3×1004CFU/ml in tissue abscess. Moreover, the genomic DNA was extracted from culture, and the amplification of Rv1044 and Rv1045 genes in 624 and 412 base pairs (between 600-700 and 400-500 in ladder), respectively, in the H37Rv and clinical samples was observed. Conclusion: It has been found that Rv1044 and Rv1045 are hypothetical proteins with 624 and 882 base pairs belonging to the AbiEi/AbiEii family of toxin-antitoxin loci. Moreover, the significant identification of TA-encoded loci genes may allow for the investigation of multidrugresistant and extensively drug-resistant tuberculosis.
Keywords: antitoxin